Greening Wastelands in Orissa - Pradhan, K. (Journal of Soil and Water Conservation, 2022)
lands are grouped into eight land- capability classes i.e. Class I to VIII taking the characteristics of soils as one of the criteria for identifying the best land use with a view to their safest and best long-time use.